Assessing millennial‐scale variability during the Holocene: A perspective from the western tropical Pacific. (1st March 2014) - Khider, D.; Jackson, C.S.; Stott, L.D.
Abstract We investigate the relationship between tropical Pacific and Southern Ocean variability during the Holocene using the stable oxygen isotope and magnesium/calcium records of cooccurring planktonic and benthic foraminifera from a marine sediment core collected in the western equatorial Pacific. The planktonic record exhibits millennial‐scale sea surface temperature (SST) oscillations over the Holocene of 0.5°C while the benthic δ18Oc document 0.10‰ millennial‐scale changes of Upper Circumpolar Deep Water (UCDW), a water mass which outcrops in the Southern Ocean. Solar forcing as an explanation for millennial‐scale SST variability requires (1) a large climate sensitivity and (2) a long 400 year delayed response, suggesting that if solar forcing is the cause of the variability, it would need to be considerably amplified by processes within the climate system at least at the core location. We also explore the possibility that SST variability arose from volcanic forcing using a simple red noise model. Our best estimates of volcanic forcing falls short of reproducing the amplitude of observed SST variations although it produces power at low‐frequency similar to that observed in the MD81 record. Although we cannot totally discount the volcanic and solar forcing hypotheses, we are left to consider that the most plausible source for Holocene millennial‐scale variability lies within the climate system itself. In particular, UCDW variability coincided with deep North Atlantic changes, indicating a role for the deep ocean in Holocene millennial‐scale variability.